Pengaruh Persepsi Pengguna Jasa Terminal terhadap Peluang Pengembangan Bisnis di Terminal Tipe A Mangkang, Kota Semarang: Studi Kasus Pada BPTD Kelas I Jawa Tengah - Muhamad Nurul Anwar; Teti Safari; Heri Usodo; Wahyu Kusuma Dewi (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to analyze the influence of terminal users’ perceptions on business development opportunities at Mangkang Type A Terminal, Semarang City, managed by the Central Java Class I Transportation Management Agency (BPTD). As a major transportation hub, the terminal functions not only as a passenger transit point but also as a strategic economic area with potential for commercial facility development. However, the utilization of business opportunities at Mangkang Terminal remains suboptimal, necessitating an evidence-based analysis of the factors that shape these opportunities. This research employs a quantitative approach using a survey method involving terminal users, including passengers, public transport drivers, and terminal visitors. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression to examine the influence of user perceptions on business potential, which includes interest in facility usage, demand for additional services, and preferences for commercial space utilization. The findings indicate that perceptions related to comfort, safety, cleanliness, accessibility, and service quality significantly affect business development opportunities. Comfort and service quality emerge as the most dominant factors driving user interest in commercial facilities. These results emphasize that improving terminal service quality can serve as an effective strategy to expand business opportunities and enhance non-tax revenue.